Ladybird Picture Books - Ugly Duckling - Mandy Ross (India WWW.Penguin.Co, 2017)
Part of the Ladybird 'Picture Books' series - a perfect introduction to fairy tales for preschoolers - it contains amusing pictures and lots of funny rhythm and rhyme to delight young children. Ideal for reading aloud and sharing with 2-4 year olds. This paperback book has 32 pages and 25 x 25 x 0.3cm
Keywords: Read Aloud -- Read Aloud